English Teachers’ Pedagogical Practice and Challenges During the Transition Era From Face-to-Face Classroom to Online Teaching - Nurul Hidayati; Sam Hermansyah; Syamsu Tang (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
The purpose of this research is to investigate the pedagogical practices and challenges faced by teachers at SMP Negeri 3 Panca Rijang during the transition from face-to-face learning to online learning. This study employs a qualitative research methodology to explore the strategies, difficulties, and challenges encountered by teachers in both face-to-face and online learning environments at SMP Negeri 3 Panca Rijang. Based on the interviews conducted with the teachers, it is evident that they face numerous challenges in adapting to and implementing online learning as well as maintaining traditional face-to-face teaching methods. Teachers are compelled to adapt swiftly and find rapid solutions to these challenges. The primary issues identified in online learning include unstable internet connections and the lack of availability of devices for all students. Solutions implemented include flexible timing for assignments, using social media groups to distribute learning materials, and providing alternative means for students to access learning, such as visiting the teacher's house or studying with nearby friends. A significant challenge remains ensuring that students understand the material thoroughly, as online classes make it difficult to monitor student engagement and participation. To address this, teachers have resorted to calling on students by name to maintain focus and attention during lessons.